The mimetic basis of pure music in Machaut's Refrain Songs: Part 2, musical abstraction - Maw, D (Cambridge University Press, 2020)
The dualistic relationship of words and music in Machaut’s refrain songs (proposed in Part 1 of this article) enables abstraction of the music from the poetic model that inspired it. This situation is at its most extreme in certain rondeaux, representatives of a genre for which a special function in Machaut’s output is argued. Studies of specific groups of songs (B9-R4 and B35-R13-R21) illustrate the gradual development and detachment of material in related compositions. Through these accounts, it can be seen that the relationship of words and music proceeds on the same fundamental basis in the seemingly melismatic rondeaux as in the syllabic virelais, despite the apparently closer connection found in these latter. The technical unity at work in Machaut’s song composition is constitutive of an aesthetic position. The abstracted musical text is an aspect of the multi-faceted voice of Machaut’s lyric œuvre and tends to subsume the poetry it sets creating an aesthetic of pure music.